1988
DOI: 10.1152/jappl.1988.65.1.373
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of bone and tendon to prolonged hindlimb suspension in rats

Abstract: The rat hindlimb suspension model was used to ascertain the importance of ground reaction forces in maintaining bone and tendon homeostasis. Young female Sprague-Dawley rats were randomly assigned to either a suspended or a nonsuspended group. After 28 days, femur bones and patellar tendons were obtained for morphological and biochemical analyses. Prolonged suspension induced a significant change in the geometric configuration of the femur middiaphysis by increasing the minimum diameter (12%) without any signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 0 publications
2
26
0
2
Order By: Relevance
“…Our values for hydroxyproline content in control rats are in agreement with previous results published for tendons and other similar connective tissues (Takacs and Verzar, 1968;Vailas et al, 1985Vailas et al, , 1988. Although long term monitoring for hydroxyproline content during tendon degeneration and regeneration has never been clearly reported, we showed that the rapid loss of hydroxyproline coincides with the accumulation of PMNs and Ms, which supports the hypothesis that leukocytes phagocytose and digest collagen during the inflammatory phase.…”
Section: Effects Of Diclofenac On Tendon Inflammation and Regenerationsupporting
confidence: 92%
“…Our values for hydroxyproline content in control rats are in agreement with previous results published for tendons and other similar connective tissues (Takacs and Verzar, 1968;Vailas et al, 1985Vailas et al, , 1988. Although long term monitoring for hydroxyproline content during tendon degeneration and regeneration has never been clearly reported, we showed that the rapid loss of hydroxyproline coincides with the accumulation of PMNs and Ms, which supports the hypothesis that leukocytes phagocytose and digest collagen during the inflammatory phase.…”
Section: Effects Of Diclofenac On Tendon Inflammation and Regenerationsupporting
confidence: 92%
“…The estimation of the ligament cell density was achieved by determining the amount of DNA using a modified method of Bonting and Jones (5) and as previously performed by our laboratory (9,38). A stock solution of 0.1 mg NaDNA (type I; Sigma-Aldrich) per 1 ml distilled H 2O was prepared and used as a standard.…”
Section: Biochemistrymentioning
confidence: 99%
“…1 In developing countries where more individuals are involved in life-long physical labor and regular exercise, sinew ruptures remain relatively uncommon. With inactivity, sinews lose collagen, 2,3 and become brittle and stiff, 4 making them prone to injury. In contrast, exercise increases the rate of collagen turnover, 5 indicating that mechanical loading is of primary importance in the maintenance of sinew function.…”
mentioning
confidence: 99%